The impact of multimedia learning approach on mastering skateboarding skills: a study among beginner skateboarders in Kuala Lumpur / Muhammad Rafiq Akmal Abd Rahman - Abd Rahman, Muhammad Rafiq Akmal (2023)
The impact of multimedia learning on skateboarding skill mastery among novice skateboarders in Kuala Lumpur is investigated in this thesis. Quantitative surveys were carried out using a mixed-methods methodology. Participants' exposure to multimedia learning resources and perceptions of their effects on skill development were evaluated via surveys. The interviews gave participants' experiences and views of multimedia learning additional context. The results support sports education by guiding the development of successful learning interventions for newbie skateboarders. The knowledge gained can help educators, trainers, and instructional designers improve skill development and maximize learning opportunities for novice skateboarders in Kuala Lumpur.